Angelica Polysaccharide Antagonizes 5-FU-Induced Oxidative Stress Injury to Reduce Apoptosis in the Liver Through Nrf2 Pathway - Zeng, Di; Wang, Yaping; Chen, Yi; Li, Danyang; Li, Guoli; Xiao, Hanxianzhi; Hou, Jiyin; Wang, Ziling; Hu, Ling; Wang, Lu; Li, Jing (Frontiers in Oncology, 2021)
Oxidative stress induced by chemotherapeutic agents induces hepatotoxicity. 5-Fluorouracil (5-FU) has been found to have a variety of side effects in the treatment of tumors, but its toxic effect on the liver and the mechanism are still unclear. Angelica polysaccharide (ASP), the main active ingredient of the traditional Chinese medicine Dang Gui, has antioxidative stress effects. In this study, we investigated the antagonistic effects of ASP on 5-FU-induced oxidative stress injury and apoptosis in the mouse liver and human normal liver cell line MIHA and the possible mechanism. Our results show that ASP inhibited the increase in Bax protein, and the decrease in Bcl-2 protein caused by 5-FU. ASP alleviated the increase in alanine aminotransferase (ALT), aspartate aminotransferase (AST), and triglyceride (TG) content; liver steatosis; and liver fibrosis induced by 5-FU. ASP restored 5-FU-induced swelling of mitochondria and the endoplasmic reticulum. 5-FU increased the expression of Keap1 and promoted its binding to NF-E2-related factor 2 (Nrf2) and reduced the nuclear translocation of Nrf2, thereby weakening the transcriptional activity of Nrf2 to inhibit the expression of HO-1; reducing the activity of GSH, SOD, and CAT to increase ROS content; and aggravating DNA damage (indicated by the increase in 8-OHdG). However, ASP reversed these reactions. In conclusion, ASP attenuated the 5-FU-induced Nrf2 pathway barrier to reduce oxidative stress injury and thereby inhibit abnormal lipid metabolism and apoptosis. This study provides a new protectant for reducing the hepatic toxicity caused by 5-FU and a novel target for treating liver injury.